PENGARUH ENTREPRENEURIAL SELF EFFICACY DAN ENTREPRENEURIAL ORIENTATION TERHADAP GREEN ENTREPRENEURIAL INTENTION - Linda Maryani; Tjutju Yuniarsih (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2022)
This research aims to test the effect of entrepreneurial self-efficacy and entrepreneurial orientation on green entrepreneurial intention. The research method used in this research is quantitative approach with explanatory survey type. This research was conducted on students of the Economic Education Study Program, Faculty of Economics and Business Education, Universitas Pendidikan Indonesia Bandung. The population in this study in number of 379 students with 195 samples of students.The results of data processing in this research shows that Economic Education students have entrepreneurial self-efficacy, entrepreneurial orientation, and green entrepreneurial intention in the high category. the results of this study also indicate that both entrepreneurial self-efficacy and entrepreneurial orientation have a significant effect on green entrepreneurial intention.